2013
DOI: 10.5812/jjm.7625
|View full text |Cite
|
Sign up to set email alerts
|

Citric Acid Production from Sugarcane Bagasse through Solid State Fermentation Method Using Aspergillus niger Mold and Optimization of Citric Acid Production by Taguchi Method

Abstract: Background: Citric acid is produced in insignificant quantities in Iran. Despite its great range of utilizations, and from another aspect, high level of production of sugarcane bagasse, the related problems arising from maintenance of this acid require thinking of a measure in the direction of its optimal usage and production. Objectives: The objective of the present study is to obtain effectual variables in producing citric acid from sugarcane bagasse through Solid State Fermentation (SSF) method using Asperg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 24 publications
0
24
0
2
Order By: Relevance
“…It is well documented that solid state fermentation processes are largely influenced by the nature of the solid substrate. The substrates are generally water insoluble polymers of cellulosic or starchy material [25]. Our study indicated that GA3 production was increased by the addition of different compounds as inducers to the media.…”
Section: Optimization Of Ga3 Production By the Taguchi Methodmentioning
confidence: 75%
“…It is well documented that solid state fermentation processes are largely influenced by the nature of the solid substrate. The substrates are generally water insoluble polymers of cellulosic or starchy material [25]. Our study indicated that GA3 production was increased by the addition of different compounds as inducers to the media.…”
Section: Optimization Of Ga3 Production By the Taguchi Methodmentioning
confidence: 75%
“…Solid state fermentation processes are largely influenced by the nature of the solid substrate. The substrates are generally water insoluble polymers of cellulosic or starchy material . The selection of a suitable solid substrate for a fermentation process is a critical factor and thus involves the screening of a number of agro‐industrial materials for microbial growth and product formation .…”
Section: Discussionmentioning
confidence: 99%
“…The substrates are generally water insoluble polymers of cellulosic or starchy material. 53 The selection of a suitable solid substrate for a fermentation process is a critical factor and thus involves the screening of a number of agro-industrial materials for microbial growth and product formation. 33 Our study revealed that glucose oxidase activity was increased by the addition to the media of different compounds as inducers.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from fruit wastes, citric acid can also be produced from agro-industrial wastes such as oil palm empty fruit bunches [142], sugarcane bagasse [143], cassava bagasse [144], and biodiesel by-products [145] through SSF. Yadegary et al [143] optimized citric acid production using sugarcane bagasse as a substrate by SSF using the Taguchi statistical method.…”
Section: Organic Acids Productionmentioning
confidence: 99%
“…Yadegary et al [143] optimized citric acid production using sugarcane bagasse as a substrate by SSF using the Taguchi statistical method. Alkaline and acid pretreatment showed an increase in the yield production of 97.81 g·kg −1 and 87.32 g·kg −1 respectively, compared with untreated sugarcane bagasse yield of 75.45 g·kg −1 .…”
Section: Organic Acids Productionmentioning
confidence: 99%